2019
DOI: 10.1177/0258042x19851649
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Training and Development Practices on Job Satisfaction: A Study on Faculty Members of Technical Education Institutes

Abstract: The study attempts to examine the relationship and impact of training and development practices on job satisfaction of employees. Universe of the study has been limited to faculty members employed at institutes providing technical education in the city of Nagpur, Maharashtra, India. A sample size of 360 faculty members was collected to represent the universe. The research was conducted in a confirmatory framework so as to examine the causal linkage among the study variables. The results depicted a positive rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…Finally, this research has proven that job satisfaction partially mediates the relationship between training and organisational performance as well as the relationship between innovation and organisational performance which supports hypothesis H6 and H7 of this research respectively. These findings validate previous results of (Paposa & Kumar, 2019;Faridi, 2017;Basir & Wahjono, 2014;Latif et al, 2013;Marsick & Watkins, 2003) who professed that training and innovation develops organisational performance due to the satisfaction gained by employees.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Finally, this research has proven that job satisfaction partially mediates the relationship between training and organisational performance as well as the relationship between innovation and organisational performance which supports hypothesis H6 and H7 of this research respectively. These findings validate previous results of (Paposa & Kumar, 2019;Faridi, 2017;Basir & Wahjono, 2014;Latif et al, 2013;Marsick & Watkins, 2003) who professed that training and innovation develops organisational performance due to the satisfaction gained by employees.…”
Section: Discussionsupporting
confidence: 90%
“…Extrinsic job satisfaction is a result of additional remunerations that emerges from superior organisational performance achieved, the capability to execute jobs, utilising the knowledge, skills, and abilities. Thus, training develops organisational performance due to the satisfaction gained by the employees (Paposa & Kumar, 2019;Faridi, 2017;Basir & Wahjono, 2014;Latif et al, 2013).…”
Section: Mediating Role Of Job Satisfactionmentioning
confidence: 99%
“…Rahayu, Rasid, and Tannady (2019) concluded that training development has a positive and significant relationship with job satisfaction. Furthermore, Paposa and Kumar (2019) also reported similar results, as they found a high degree of correlation between training and development and job satisfaction. Thus, the current study examines the relationship between training and development and job satisfaction in the Yemeni banking sector by proposing the following hypothesis: H2: There is a significant relationship between Training and Development and employee Job Satisfaction in Yemen's Banking sector…”
Section: The Effect Of Training and Development On Job Satisfactionsupporting
confidence: 58%
“…The appropriate ratios of offline and online learning are 75% and 25%, respectively. The training and development for faculty in technical education is emphasized in the research works of Paposa and Kumar (2019). Educational institutes should focus on training faculty in techniques and delivery of online learning, implementing curriculum changes suitable to online and employing emerging ICT technologies.…”
Section: Discussionmentioning
confidence: 99%